Karakteristik Fisik, Kimia, dan Sensoris Siomay Ayam dengan Penambahan Bayam (Amaranthus tricolor L.) - Christantio, Michelle Anabelle; Yusasrini, Ni Luh Ari; Darmayanti, Luh Putu Trisna (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i04.p15, 2023)
Chicken shumai is dim sum made by mixing chicken meat with tapioca and seasonings, then wrapped in wonton skins and cooked through a steaming process. Chicken shumai is high in carbohydrates, protein, and fat, but lacks fiber and bioactive compounds. Thus, it is needed to add other ingredients such as spinach to increase the fiber content and bioactive compounds of shumai, along with following the trend of a healthy lifestyle in society. This study aims to determine the effect of spinach addition on the characteristics of chicken dumplings and to determine the amount of spinach addition that can produce chicken shumai with the best characteristics. This study used a completely randomized design with spinach addition treatment consisting of 7 levels, namely 0, 10, 20, 30, 40, 50, and 60 percent. Data were then analyzed by variance analysis and if the treatment had a significant effect, it was continued with the Duncan Multiple Range Test. The results showed that the addition of spinach had a significant effect (P<0.05) on moisture content, ash content, protein content, crude fiber content, antioxidant capacity, texture, and sensory properties of the product, but no significant effect (P>0.05) on product fat content. The treatment of adding 10 percent spinach produced shumai with the best characteristics, namely with criteria of water content 55,41 percent, ash content 1,18 percent, protein content 10,51 percent, fat content 3,72 percent, crude fiber content 1,99 percent, antioxidant capacity 16,69 mg/L GAEAC, texture or hardness 6,53 N, with color, aroma, taste, texture, and overall acceptance preferred by the panelists.